Prevalence and Zoonotic Potential of Giardia intestinalis in Dogs of the Central Region of Mexico - Elsa M. Godínez-Galaz; Nerina P. Veyna-Salazar; Andrea M. Olvera-Ramírez; Feliciano Milián-Suazo; Claudia A. Perea-Razo; Rodolfo Bernal-Reynaga; Germinal J. Cantó-Alarcón (Animals, 2019)
Giardia intestinalis is a protozoan of worldwide distribution capable of infecting a large number of species, including humans and domestic animals. Dogs represent a risk to public health due to cross-infections by the zoonotic assemblages. However, there is little information concerning the prevalence and frequency of this parasite and its assemblages in dogs of the central region of Mexico, thus this study aimed to contribute to this matter. A total of 402 feces samples from dogs of different settings (shelter, breeding establishments, domestic and stray) were obtained and direct coproparasitoscopic examination by flotation revealed a prevalence of 25%. PCR was performed for amplification of the β-Giardin gene, to which 24 samples were positive. Assemblages were obtained through RFLP analysis, using enzymes Hae III to obtain the main genotypes (A−G), and Hha I to subtype assemblage A. All 24 samples were genotyped as assemblage A, with 83% as AI and 17% as AII. Thus, these findings confirm that dogs in the central region of Mexico are a risk for zoonotic transmission of this parasite, emphasizing the importance of a much needed control of the disease in this species.